Evaluation of Antifungal, Hemolytic and Cytotoxic Potential of Ethyl Acetate Extract of a New Marine Streptomyces sp. AIAH-10 (Bangladesh Pharmaceutical Journal, 2016)
To face newly generated diseases, search for new, safe and effective bioactive molecules is highly warranted. The marine microbial flora may be a potential source of such molecules. The present study was designed to isolate marine microorganisms (AIAH-1 to AIAH-29) from the soil of mangrove forest Sundarbans, Bangladesh by serial dilution method using isolation media. Among them, AIAH-10 was selected for further study due to its promising antibacterial activity (done by streak plate and plug technique method) against a series of pathogenic bacteria. On the basis of morphological, cultural and biochemical analysis, the strain AIAH-10 belongs to Streptomyces sp. Secondary metabolites of the strain was obtained by small scale fermentation process. Antifungal activity of the extracts was performed by disc diffusion method. The crude ethyl acetate extract (50µg/disc) showed significant antifungal activity against Aspergillus niger, Candida albicans and Saccharromyces cerevaceae (14, 12 and 10 mm zone of inhibition respectively). No hemolytic activity was found of the extracts towards the human erythrocytes. During cytotoxic study against brine shrimp nauplii (Artemia salina), a dose dependent mortality rate was observed. A 100% larva mortality rate was recorded in 40µg/ml and more where as LC50 was found to be 6.61µg/ml.Bangladesh Pharmaceutical Journal 19(1): 37-43, 2016